Age at menopause: A fundamental data of interest to acquire in female patients' anamnesis. (15th July 2016) - Sciomer, Susanna; De Carlo, Carlotta; Moscucci, Federica; Maffei, Silvia
Abstract: Although menopause is a universal phenomenon among women, the timing of the onset and the duration of the menopausal transition and the timing of the final menstrual period are not so codified. Compelling evidence supports the idea that the different impact of cardiovascular disease and the differences in vascular biology in men and women may be, at least in part, related to the cardiovascular and metabolic effects of sex steroid hormones. Indeed, androgens and estrogens influence a multitude of vascular biological processes and their cardiovascular effects are multifaceted. Gender pharmacology has proven that men and women have tiny but not paltry different effects to the same drug. Estrogens exert potential beneficial effects on the cardiovascular system in both sexes. It is evident that there is a need for the physician who approaches the female patient, to stress the main anamnestic data concerning her hormonal life starting from menarche, through pregnancy, until menopause. Thus it will be not only a formality becoming a cornerstone of the first doctor-patient relationship, both for in- and outpatient, we will have a clear and complete representation of the etiology and evolution of cardiovascular diseases that increasingly afflict the female gender.